(untitled) (University of Khartoum Journal of Agricultural Sciences, 2025)
The study was undertaken to generate broad-base data on thehydrothermal regimes in a Vertisol under Acacia senegal in Al Rawashdaforest, 35 km northeast Al-Gedarif town. The indicators measured fordescribing the moisture regime were rainfall, infiltration and evaporationrates from U.S. Class A pan, soil moisture storage and actualevapotranspiration. In 1997, the total rainfall was 403 mm, 48% wasreceived in August and 82% was received in July, August and September.The soil was fully recharged with moisture during June-September,depleted and desiccated during October-March and started to rewet inApril-May. The daily evaporation ranged from 2.9 to 5.6 mm in autumn,7.5 to 13.6 mm in winter and 12.8 to 16.0 mm in summer. The soilmoisture storage was lowest in 14th May and highest in 5 th September,1997. Although rainfall reduced the vapour pressure gradient, it increasedthe availability of water to the evaporating site and consequentlyincreased evaporation. Thus, mean monthly evaporation (Em, mm)increased significantly (P = 0.05) with increase of mean monthly rainfall(Rm, mm) as shown by the following power relationship: Em = 1738 Rm0.5402 (r2 = 0.790). The pooled infiltration rate (IR) as a function of timefor the two sites in three successive months’ best fitted the following